2014
DOI: 10.1051/0004-6361/201322788
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Milky Way bulge at high resolution: the 3D dust extinction, CO, and X factor maps

Abstract: Context. Three dimensional interstellar extinction maps provide a powerful tool for stellar population analysis. However, until now, these 3D maps were rather limited by sensitivity and spatial resolution. Aims. We use data from the VISTA Variables in the Via Lactea survey together with the Besançon stellar population synthesis model of the Galaxy to determine interstellar extinction as a function of distance in the Galactic bulge covering −10 • < l < 10 • and −10 • < b < 5 • . Methods. We adopted a recently d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
126
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 111 publications
(133 citation statements)
references
References 51 publications
7
126
0
Order By: Relevance
“…This anti-correlation reflects that in the diffuse (low-W CO ) region CO molecule is photo-dissociated more effectively than H 2 , and therefore X CO increases. This trend is consistent with the result in Cotten & Magnani (2013); Schultheis et al (2014), and we can say that the spatial distribution of X CO can be well calculated by using the present method.…”
Section: 87±004supporting
confidence: 92%
“…This anti-correlation reflects that in the diffuse (low-W CO ) region CO molecule is photo-dissociated more effectively than H 2 , and therefore X CO increases. This trend is consistent with the result in Cotten & Magnani (2013); Schultheis et al (2014), and we can say that the spatial distribution of X CO can be well calculated by using the present method.…”
Section: 87±004supporting
confidence: 92%
“…This is supported by the 3D dust extinction maps by Schultheis et al (2014), who found a large jump in extinction at low latitude located at a distance of about 6 kpc along the line of sight to the bulge. This may be the signature of a dust ring as seen in other galaxies that have suffered recent mergers (such as M 64 or NGC 5128).…”
Section: Discussionsupporting
confidence: 60%
“…We estimate -= ( ) E B V  1.16 0.12. Three-dimensional reddening maps of the Galaxy (Schultheis et al 2014) imply that V1324Sco is >6.5 kpc away (see also Munari et al 2015 for similar results). V1324Sco's location near or beyond the Galactic bulge implies that it is significantly more gamma-ray luminous than other gamma-ray-detected novae ( ǵ L 2 10 36 erg s −1 in the energy range 100 MeV-10 GeV, exceeding other novae by order of magnitude; Ackermann et al 2014;Finzell et al 2015).…”
Section: V1324scomentioning
confidence: 76%